2016
DOI: 10.1007/s00467-016-3421-6
|View full text |Cite
|
Sign up to set email alerts
|

Hyperechogenic kidneys and polyhydramnios associated with HNF1B gene mutation

Abstract: In the absence of maternal diabetes, HNF1B mutation can be associated with polyhydramnios, probably due to fetal polyuria. Thus, HNF1B mutation represents a differential diagnosis of polyhydramnios associated with hyperechogenic (and sometimes enlarged) kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
(24 reference statements)
2
7
0
Order By: Relevance
“…Inefficient expression of HNF1B in the region of 17q12 is known to be a predominant factor leading to renal disease, which may result in fetal polyuria and polyhydramnios. The most common ultrasound finding in fetuses with 17q12 deletion was hyperechogenic kidneys [ 20 ], which was also present in our case. Thus, a view has been proposed when hyperechogenic kidney and polyhydramnios were observed prenatally, a possible diagnosis of 17q12 deletion should be considered [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 73%
“…Inefficient expression of HNF1B in the region of 17q12 is known to be a predominant factor leading to renal disease, which may result in fetal polyuria and polyhydramnios. The most common ultrasound finding in fetuses with 17q12 deletion was hyperechogenic kidneys [ 20 ], which was also present in our case. Thus, a view has been proposed when hyperechogenic kidney and polyhydramnios were observed prenatally, a possible diagnosis of 17q12 deletion should be considered [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 73%
“…kidneys. 26 In this study, a heterozygous missense mutation (PKD1: In our study, we reported an incidental finding (PPM1D: c.1434delC) in a fetus with right renal dysplasia, which made a counseling challenges and deep ethical questions in the prenatal setting,…”
Section: Discussionmentioning
confidence: 68%
“…Accordingly, 7 cases were diagnosed with variations in PKD1 gene and 15 cases were affected by ARPKD 25 . Furthermore, Leire Gondra reported that HNF1B mutation represents the leading cause of polyhydramnios associated with hyperechogenic (and sometimes enlarged) kidneys 26 . In this study, a heterozygous missense mutation ( PKD1 : c.6571C > T) in a fetus with bilateral echogenic kidneys and two frame shift deletions (PKHD1:c.8301del and c.4481del) in a fetus with bilateral hyperechogenic and enlarged kidneys combined with oligohydramnios were identified.…”
Section: Discussionmentioning
confidence: 99%
“…2 Other fetal malformations have been described, such as hyperechoic kidneys associated with a mutation in the HNF-1-β gene. 18 Placental anomalies are relatively common and should be investigated by ultrasound. In our series, we found one case of chorioangioma (benign tumor of the placenta) which can cause fetal hydrops if large.…”
Section: Discussionmentioning
confidence: 99%
“…It is to notice that none of the pathologies in this series were cardiac, which is one of the most common pathologies to develop hydramnios 2 . Other fetal malformations have been described, such as hyperechoic kidneys associated with a mutation in the HNF‐1‐ β gene 18 . Placental anomalies are relatively common and should be investigated by ultrasound.…”
Section: Discussionmentioning
confidence: 99%